Serological diagnosis of infection with human herpesvirus type 6. Issue 6718 (20th January 1990) - Irving, W L; Cunningham, A L
Abstract : OBJECTIVE--To identify clinical consequences of acute human herpesvirus type 6 infection by hypothesising that the virus will induce similar clinical syndromes to cytomegalovirus. DESIGN--Examination of consecutive serum samples from patients with illnesses compatible with acute cytomegalovirus infection or exanthem subitum by indirect immunofluorescence for the presence of antibodies to human herpesvirus type 6. An IgG absorption step was included to avoid false positive and negative results for IgM. The criterion standard for diagnosis of human herpesvirus type 6 infection was the presence of IgM human herpesvirus type 6 antibody (titre greater than 20) and a rising titre of IgG human herpesvirus type 6 antibody without serological evidence of alternative infection. SETTING--Routine viral diagnostic and reference laboratory in the largest teaching hospital in Sydney. PATIENTS--341 Consecutive serum samples were analysed from patients with hepatitis (147 samples); infectious mononucleosis-like illness (106); screens for toxoplasma, other viruses, rubella, cytomegalovirus, and herpesvirus (38); fever in an immunocompromised patient (eight); unusual neurological (nine) or haematological syndromes (14); splenomegaly (six); and rash in a child (13). RESULTS--Three cases of acute human herpesvirus type 6 infection were identified: in one patient aged 65 with a previous diagnosis of acute non-A non-B hepatitis, one aged 25 with a glandular fever-like illness, and one aged 6 with a glandular fever-like illness. All three illnesses resolved completely. 15 Further serum samples were positive for human herpesvirus type 6 antibody but were also diagnostic for acute infection with other viruses (cytomegalovirus (nine), Epstein-Barr virus (three), and HIV (one] or had a titre of IgM human herpesvirus type 6 antibody less than 20 (two). CONCLUSIONS--Acute human herpesvirus type 6 infection in immunocompetent patients may result in a mononucleosis-like illness or an acute but self limiting hepatitis.